Genetic Algorithm based Optimal Service Selection of Composition in Middleware using QoS Correlation - Dongre, Yashwant; Patil, Pramod (International Journal of Intelligent Systems and Applications in Engineering, 2023)
A key role is played by service composition, a critical technique for integrating sophisticated web applications in service oriented architecture. The service selection procedure highlighted Quality of Service as a necessary criterion for the optimum selection of services for the composition process. It can be challenging to find functionally equivalent services that meet the user’s nonfunctional requirements. Web services employ Software as a Service to create web applications. When selecting the best services from the input set, we first apply the minimal services technique to decrease the quantity of unsuitable services in the candidate services set. The suggested Genetic Algorithm (GA) correlation-based methodology has a shorter calculation time than the conventional GA-based approach, and it outperforms the current GA-based method, according to the findings of the experimental implementation and statistical analysis.